BIOPRODUKSI (+)-EPIEPOKSIDON OLEH JAMUR ENDOFIT Diaporthe sp. E YANG DIISOLASI DARI TANAMAN TEH - Andria Agusta (BERITA BIOLOGI, 2006)
Six kinds of the endophytic fungi have been isolated from a tea plant. One of them identified as Diaporthe sp. E based on their morphological characters and rDNA sequens. By the cultivation in liquid medium, the endophytic fungus produced (+)-epiepoxydon besides gentisyl alcohol and toluquinol.